Aktivitas Daya Hambat Limbah Daging Buah Kopi Robusta ( Coffea robusta L.) Aceh terhadap Bakteri S.aureus dan E.coli - Muhammad Ridwan Harahap (Jurnal Kesehatan, 2018)
Coffee fruit flesh is a waste that coffee farmers use as animal feed only, even though has a composition such as carbohydrates, proteins, fiber, minerals, water, protein, caffeine, and polyphenols. These compositions are very useful for cosmetic and pharmaceutical industries. This study was a research on the use of waste of Aceh’s Robusta fruit flesh (Coffea robusta) on the ability to inhibit the bacteria S-aureus and E.coli as the basic ingredients of the cosmetic face mask of halal products. The samples used were from Takengon city. The skin of the coffee beans was peeled, cleaned and extracted with methanol for about 3 x 24 hours. Further concentrated until obtained extract concentrated. The resulting extracts were tested phytochemically. Variations of extracts concentration on water solvents were 1%, 2%, and 3%. The antibacterial activity was tested by the diffusion method which used the disc. The result showed inhibitory zone to E.coli bacteria at 1%, 2%, 3% concentration were 6,5 mm, 7.2 mm and 7.8 mm respectively. While in S.aureus at a concentration of 1%, 2%, 3% were 15.1 mm, 15.3 mm and 15.5 mm respectively. The best variation of the concentration of Robusta coffee fruit flesh extract (Coffea robusta) in this study on the growth of S-aureus and E.coli bacteria was 3%.